Nonsense suppressor and antisuppressor mutations at the 1409-1491 base pair in the decoding region of Escherichia coli 16S rRNA. - Gregory, S T (1995)
Using a genetic selection for suppressors of a UGA nonsense mutation in trpA, we have isolated a G to A transition mutation at position 1491 in the decoding region of 16S rRNA. This suppressor displayed no codon specificity, suppressing UGA, UAG and UAA nonsense mutations and +1 and -1 frameshift mutations in lacZ. Subsequent examination of a series of mutations at G1491 and its base-pairing partner C1409 revealed various effects on nonsense suppression and frameshifting. Mutations that prevented Watson-Crick base pairing between these residues were observed to increase misreading and frameshifting. However, double mutations that retained pairing potential produced an antisuppressor or hyperaccurate phenotype. Previous studies of antibiotic resistance mutations and antibiotic and tRNA footprints have placed G1491 and C1409 near the site of codon-anticodon pairing. The results of this study demonstrate that the nature of the interaction of these two residues influences the fidelity of tRNA selection.